Sofosbuvir plus velpatasvir combination for the treatment of chronic hepatitis C in patients with end stage renal disease on renal replacement therapy: A systematic review and meta‐analysis. Issue 1 (14th September 2021) - De, Arka; Roy, Akash; Verma, Nipun; Mishra, Saurabh; Premkumar, Madhumita; Taneja, Sunil; Singh, Virendra; Duseja, Ajay
ABSTRACT: Introduction: Sofosbuvir (SOF) and velpatasvir (VEL) is a pan‐genotypic regimen for the treatment of Hepatitis C virus (HCV) infection. The data on the efficacy and safety of this regimen is end‐stage renal disease (ESRD) is scanty. This systematic review and meta‐analysis was done to ascertain the efficacy and safety of SOF and VEL in patients with chronic Hepatitis C (CHC) and ESRD on renal replacement therapy (RRT). Methods: Systematic search of Pubmed, Embase, Scopus, and Google Scholar was conducted using the search term (end‐stage renal disease OR renal replacement therapy OR chronic kidney failure OR severe renal impairment OR chronic kidney disease OR haemodialysis OR dialysis OR peritoneal dialysis) AND (sofosbuvir OR velpatasvir OR NS5A inhibitors OR directly acting antivirals). Pooled sustained virologic response (SVR) and adverse event rates with 95% confidence intervals were estimated. Results: Seven studies (410 patients with CHC and ESRD on RRT) fulfilled our eligibility criteria. The overall pooled SVR rate of SOF and VEL in patients with HCV on RRT was 97.69% (95% CI: 95.71 to 98.92). There was no significant heterogeneity (I 2 : 39.3%, p ‐value of Cochran's Q = 0.13) among the studies. The pooled estimate of efficacy of SOF‐VEL combination among patients with cirrhosis was 91.94% (95% CI 77.03–98.52). Pooled SVR rates in genotype 3 infection [94.6%, (95%: CI 81.3–99.4)] was comparable to that in those with documented non‐genotype 3 infection [94.63%, (95% CI 87.12–98.44)]. No serious adverse event attributable to SOF and VEL was reported in the included studies. Conclusion: The fixed‐dose combination of SOF and VEL is effective and safe in CHC patients with ESRD on RRT. SUMMARY AT A GLANCE: This systematic review/meta‐analysis revealed collective evidence that the sofosbuvir/velpatasvir combination is efficacious and safe for HCV eradication in patients on kidney replacement therapy.